Finite element analysis of maxillary orthodontic therapies with variable alveolar bone grafts under occlusal forces in patient with unilateral cleft lip and palate - Zhang, Zhi; Li, Chenghao; Zheng, Qian; Shi, Bing; Liu, Renkai (Frontiers in Bioengineering and Biotechnology, 2024)
Objective To investigate the biomechanical effects of maxillary orthodontic treatment on different alveolar bone grafting positions loaded with occlusal forces in an unilateral cleft lip and palate (UCLP) patient. Methods Finite element analysis was employed to simulate clinical scenarios more accurately by loading with occlusal forces on 8 bone-grafted models during maxillary orthodontic treatment. Displacement and von Mises stress pattern during maxillary protraction, expansion, and combined protraction and expansion were analyzed. Results The seven bone-grafted models exhibited significantly smaller horizontal displacements at the non-cleft side landmarks during maxillary protraction and expansion compared to non-bone grafted models. Additionally, alveolar cleft bone grafted in the upper 1/3 and middle 1/3 exhibited greater asymmetry displacement and stress under maxillary protraction and expansion. Conclusion The study highlights the necessity of considering occlusal forces in finite element study on orthodontic therapies for UCLP patients. The upper 1/3 and middle 1/3 bone graft conditions may require secondary bone graft supplementation to ensure the effectiveness of maxillary orthodontic treatment.